Science Interactive E-Book Based Problem-Based Learning to Improve Creative Thinking Skills: Needs Analysis Based on Teacher Perception - Andan Yani; Dadan Rosana (Postgraduate, University of Mataram, 2024)
The sophistication of technology today has been widely used by educators to teach and as a means for students to learn. The development of technology, especially in the field of education, then it requires teachers to have media and teaching materials that attract student's attention to learning. This study aims to analyze teachers' needs for interactive science e-books based on Problem-Based Learning (PBL) in learning. This research is qualitative research with a case study approach. Data collection uses observation and interview techniques. Interviews were conducted with two science teachers from SMP Negeri 3 Depok and one science teacher from SMP Negeri 11 Yogyakarta. The results of this study are aspects of the learning process of students tend to be passive with low creative thinking skills, the aspect of using teaching materials has never used interactive e-books for learning, the aspect of using teaching materials has never been integrated with the PBL learning model. Based on the results of data analysis, teachers need PBL-based science interactive e-books to improve students' creative thinking skills.